THE INFLUENCE OF TRANSACTIONAL LEADERSHIP AND TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE AND WORK MOTIVATION AS A MEDIATION VARIABLE AT PT. PUPUK ISKANDAR MUDA - Cut Nabilla Mutiza Zahap; Faisal Matriadi; Mariyudi; Marbawi; Ikramuddin; Yulius Dharma (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to examine the influence of transactional leadership and transformational leadership on the work motivation and performance of PT. Pupu. The data in this research were 140 employees who responded to the questionnaire distributed via Google Forms. The data analysis tool uses Structural Equation Modelling which is operated with Amos. The research results show that transactional leadership styles and transformational leadership have a significant effect on work motivation and employee performance. Work motivation also significantly increases employee performance. And in testing the mediating effect of work motivation as a full mediating variable between transactional leadership and transformational leadership on the performance of PT employees. Iskandar Muda Fertilizer. It is hoped that the results of this research will provide an important contribution to stakeholders in developing employee management strategies as an important resource for every organization.